DAMPAK KINERJA PEGAWAI TERHADAP KUALITAS PELAYANAN PUBLIK DI PDAM KOTA BOGOR - Heryati, Ade (Administratie: Jurnal Administrasi Publik, 2019)
The quality of public services at the Bogor Regency PDAM Office is still considered problematic. The existence of several complaints due to water outages and clean water quality is still there. Some experts claim that employee performance influenced the quality of public services. Therefore, this study aims to: analyze the performance of employees at the PDAM Office, Bogor Regency; analyzing the quality of public services at the PDAM Office, Bogor Regency; examine whether there is an effect of employee performance on the quality of public services. The method used in this study is a correlational method with a quantitative approach, which is looking for relationships (the effect of one variable on another variable. The study results indicate that the performance of employees at the PDAM Office, Bogor Regency, is considered to be quite good, and the quality of public services is also quite good. Statistical test results show that there is a significant influence on employee performance on the quality of public services.